Advances in Biomedical Infrastructure 2013 Proceedings of International Symposium on Biomedical Data Infrastructure (BDI 2013) - Sidhu, Amandeep S.; Dhillon, Sarinder K. (Studies in Computational Intelligence, 2013)
Current Biomedical Databases are independently administered in geographically distinct locations, lending them almost ideally to adoption of intelligent data management approaches. This book focuses on research issues, problems and opportunities in Biomedical Data Infrastructure identifying new issues and directions for future research in Biomedical Data and Information Retrieval, Semantics in Biomedicine, and Biomedical Data Modeling and Analysis. The book will be a useful guide for researchers, practitioners, and graduate-level students interested in learning state-of-the-art development in biomedical data management.